Fadiga muscular: análise dos músculos orbiculares da boca e mastigatórios de crianças de 6 a 12 anos de idade - Stella, Angela Ruviaro Busanello (2014)
This research aimed to study the fatigue of the orbicularis oris muscles and masticatory muscles, by analyzing the median frequency of the electromyographic signal, considering the breathing mode, the facial growth pattern and age. Also aimed to compare fatigue by electromyographic evaluation with referred fatigue time by children. For this purpose, were selected 70 children between six and 12 years old, of both sexes, that suited the study criteria. Underwent speech, cephalometric, otorhinolaringology, dentistry and body mass index. Electromyographic evaluation was performed in two evaluation protocols. Protocol of the orbicularis oris muscles, children should hold dumbbells lip 40, 60 and 100gr as well as lip exerciser until the feeling of fatigue these muscles. As for the masticatory muscles, the children should chewing gum portion and positioned bilaterally in the oral cavity to the feeling of fatigue these muscles. Subsequently, the median frequency analysis was performed on four different times for each musculature, 5, 10, 15 and 20 seconds for the orbicularis oris muscle, and 15, 30 , 45 and 60 seconds for the masticatory muscles. Were also recorded the referred fatigue time to as fatigue by children. Data were analyzed by ANOVA - repeated measures (post - hoc Tukey), Kruskal-Wallis test and Mann- Whitney U test. As results showed that: the orbicularis oris muscles showed a significant decrease in the median frequency farrowing the five seconds of activity, but regardless of the comparison between groups; when were made these comparison, muscles studied, in their respective protocols, showed no significant decrease; the reported time to the feeling of muscles orbicularis oris fatigue was lower in mouth breathers and children of age group one. When comparing orbicularis oris and masticatory muscles fatigue by electromyography and the reporting of children, in all groups, the perception occurred after the decrease of the median frequency. Thus, it is concluded that the physiological fatigue of the muscles was not influenced by breathing mode, the facial growth pattern, the association of them and age group, but the perception of muscles orbicularis oris fatigue was influenced by the breathing mode and age. The physiological fatigue of the orbicularis oris muscles preceded the reporting of fatigue time. Although there was no physiological fatigue for masticatory muscle, occurred the reporting of fatigue these muscles.